Development The Tourism Industry In Theeqar City And Future Horizons - khalaf, Kasem Jabar (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تنمية القطاع السياحي في محافظة ذي قار وافاقه المستقبلية قاسم جبار خلف تعد صناعة السياحة من اهم الصناعات العالمية، اذ اصبحت صناعة العصر والمستقبل، ويحتل هذا النشاط مكانة مهمة في اقتصاديات الدول التي تدرك اهميته وتوليه الاهتمام المناسب باعتباره رافد من روافد التنمية الاقتصادية ، ومحافظة ذي قار التي تمتلك الكثير من مقومات الجذب السياحي، الا انها لم تلق الاهتمام المطلوب والمناسب لها ، وتواجه العديد من العقبات والتحديات التي ماتزال تواجه التنمية السياحية. وعليه ينبغي تفعيل هذا القطاع الحيوي في المحافظة والتفكير الجدي بالتخطيط لوضع استراتيجية واضحة المعالم للتنمية السياحية، ولهذا الغرض يهدف البحث الى التعرض لواقع القطاع السياحي ومقومات جذبه، واهم العقبات التي تواجه التنمية السياحية، ثم الافاق المستقبلية لها. The tourism industry of the most important global industries , as industry has become the age and the future, and occupies this activity an important place in the economies of countries that recognize the importance and taking appropriate attention as a tributary streams of economic development , and ThiـQarGoverment , which has a lot of potential tourist attractions , but it did not receive the required attention and appropriate, and faced many obstacles and challenges that are still facing the development of tourism. And it should activate this vital sector in the Government and thinking seriously planning to develop a clear strategic for tourism development , and for this purpose research aims to exposure to the reality of the tourism sector and the ingredients lured , and the most important obstacles facing the development of tourism, then its future prospects.